Using IT-Enabled Dynamic Capabilities to Develop Firm Inventive Capability and Business Process Agility: The Moderating Effect of aTumultuous Surroundings - Sudarnice; Zainul Wasik; Lia Febria Lina (PT. Mawadaku Sukses Solusindo, 2024)
Businesses today must be flexible and creative in order to adapt to the ever-changing business circumstances. This study suggests that IT-enabled Dynamic Capabilities (ITDC) are used to shape firm business process agility and firm innovative capabilities in a turbulent environment. It does this by drawing on the multi-theoretic lens. The suggested model has a favorable and significant correlation, according to a study of 254 IT and business professionals from Indonesia’s companies. The relationship between ITDC and agility is greatly tempered by marketing and technological upheaval. Comparably, marketing turbulence is also significantly mild. However, in contrast to expectations, technological turbulence has a negligible moderating influence on the link between ITDC and business inventive capabilities. This study demonstrates how firm agility and innovative capability mitigate the impact of ITDC on business performance. Practical ramifications and theoretical anchoring are also covered.